Optimizing sustainable basil cultivation with smart-monitoring: a comparative study of biochar and soilless growth media - Sirjana Adhikari; Michael Vernon; Scott Adams; Lawerence Webb; Wendy Timms (Biochar)
Abstract This study evaluated the efficiency of different soilless growth media for sustainable basil cultivation compared to traditional potting mix with continuous monitoring. This paper presents a novel approach of continuous physico-chemical monitoring of basil growth using Internet of Things (IoT) enabled smart growth cabinets. Six growth media combinations—sand, coir, and biochar (unsoaked and nutrient-enriched), sand, coir, and perlite, and potting mix with 10% and 20% biochar—were tested over 30 days under controlled conditions, with potting mix as the control. The pH, electrical conductivity and cation exchange capacity of growth mixes were analyzed before and after, along with key growth metrics such as root length, shoot length, leaf number, fresh and dry plant weight and leaf area index (LAI) were analysed. Results indicated that incorporating 10 to 20% biochar into potting mix optimally enhanced basil growth, with significant improvements in root development and the LAI of the plant. Biochar soaked in nutrient solution demonstrated three times higher plant weight compared to unsoaked biochar, indicating the potential of biochar as a slow-release nutrient matrix. Despite the high exchangeable potassium and sodium of biochar, calcium and magnesium remained dominant in the potting mix, indicating the need for optimising biochar use as a horticultural growth media according to the plant type chosen. Replacement of 10 to 20% of potting mix by biochar supports the circular economy goals by enhancing plant growth and sequestering carbon. Graphical Abstract